Braindrain und Bologna-Drain – Räumliche Implikationen der Bologna-Reform und Auswirkungen auf ländliche Räume. Eine Analyse am Beispiel der Justus-Liebig-Universität Gießen - Gareis, Philipp; Diller, Christian; Huchthausen, Henning (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
This article deals with reasons and spatial distribution patterns of the choice of location of undergraduates and students and the connected spatial impacts on the regional development, especially in rural regions in Germany. First, the international state of research is presented for the choice of location of students on different points of time of their educational path. An analysis of regional statistical data linked to the finding that higher education institutions in rural regions are not able to create the same stock of students as urbanised areas, but rural regions have better chances for economic development in the presence of a higher education institution. The number of students in rural areas with higher education institutions increased even more than in sareas or metropolises. However, the brain drain of highly qualified manpower from rural regions will increase after their years of study. This is caused by a better fitting skill profile in more densely populated areas for highly skilled workforce as well as for the supply of these jobs. Whether these tendencies already start during the transition from the bachelor to master degree will be examined with data from the Justus-Liebig-University Gießen, a university in a rural region. With a view to the future development the hypothesis of the bologna drain is introduced. It implies that the transition from bachelor to master, which did not exist in Germany before the year 2000, locations to study vary a lot in their development and especially rural regions loose in the competition for brilliant minds.
Keywords: Choice of location for studies; Bologna reform; Mobility; Bologna drain; Rural regions